O006 Acute effects of combined cannabidiol (CBD) and ∆9-tetrahydrocannabinol (THC) in insomnia disorder: A randomised, placebo-controlled trial using high-density EEG. (9th November 2022) - Suraev, A; McGregor, I; Marshall, N; D'Rozario, A; Kao, C; Gordon, C; Grunstein, R; Hoyos, C
Abstract: Introduction: Medicinal cannabis is often cited as a popular alternative to common sleep aids; however, there are limited studies using complex sleep EEG methods examining its' effects in insomnia disorder. Methods: Twenty patients (16 female; median [IQR] age, 47 [13.8] years) with insomnia disorder (mean ISI=20.8) completed two 24-hour in-laboratory visits during which they received a single oral dose of 'CBD/THC' containing 200 mg cannabidiol (CBD) and 10 mg delta9-tetrahydrocannabinol (THC) or placebo. Co-primary outcomes were total sleep time (TST) and wake after sleep onset (WASO). Secondary outcomes included next-day neurobehavioural function and sleep microarchitecture metrics determined using overnight polysomnography with 256-channel high-density EEG. Results: Compared to placebo, CBD/THC significantly decreased TST (-24.5 min, p=0.047) with no significant change to WASO (+10.7 min, p=0.422). CBD/THC significantly decreased time spent in REM sleep (-33.9min, p<0.001) and increased REM sleep latency (+65.6 min, p=0.008). Preliminary high-density EEG analysis revealed increased alpha activity during REM sleep overlying the parietal cortex (p<0.05). CBD/THC did not impair next-day (+12 h post-treatment) cognitive performance, alertness or simulated driving performance (all p's>0.05). Eighty-five mild, non-serious, adverse events were reported (55 during CBD/THC; most common dry mouth, drowsiness, and fatigue). Conclusions: An acute dose of 200 mg CBD and 10 mg THC reduced TST and the time spent in REM sleep. Analysis of all high-density EEG outcomes is ongoing. CBD/THC did not affect next-day performance. Further research is required to determine the impact of chronic cannabinoid dosing on REM sleep and other objective sleep outcomes in insomnia disorder.